Sakramenty w przekazie wiary Kościoła o Jezusie Chrystusie w świetle encykliki Lumen fidei - Rossa, Piotr (Włocławskie Wydawnictwo Diecezjalne, 2013)
The article presents a reflection of the encyclical Lumen fidei on the role of the Sacraments in the transmission of faith. They are understood in light of this document as one of the forms of the Church’s communal memory. Of all the Sac-raments, Baptism and Eucharist are the most foundational ones in the experience of encountering Christ and journeying toward Him who is the end, toward whom man is striving.
The sacraments in the transmission of the Church's faith in Jesus Christ in light of the encyclical Lumen fidei
Keywords: sakrament; Kościół; wiara; Jezus Chrystus; chrzest; tożsamość; eucharystia; Lumen fidei; Franciszek papież